Implementation of Religious Extracurricular Activities to Increase the Success of Islamic Education in Islamic Boarding Schools - Tasya Dwi Ulia Sari; Ikhwan Aziz Q; Nurul Aisyah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Religious extracurricular activities in Islamic boarding schools play an important role as a means of strengthening Islamic Religious Education (PAI), not only in the cognitive aspect but also in the affective and psychomotor domains. However, their implementation still faces several challenges, such as limited supervisors, lack of method variation, and suboptimal evaluation systems. This study aims to describe the implementation of religious extracurricular activities and to analyze their level of effectiveness in improving Islamic Religious Education in pesantren. The research uses a qualitative approach with a descriptive method, and data are collected through observation, interviews, and documentation. The results show that the implementation of religious extracurricular activities has been carried out through planning, implementation, and evaluation stages, although it has not been fully optimal. These activities contribute significantly to improving the success of Islamic Religious Education, especially in the affective and psychomotor aspects, such as increased discipline in worship, religious attitudes, and practical religious skills of students. However, more systematic management and measurable evaluation are still needed to achieve optimal outcomes